Tláloc Felino... Jaguar the Puma? - Chávez Servano, Hugo Iván (2025)
Introduction: Tláloc, the Nahuatl deity of rain and fertility, arrived in Central America with Nahua migrations, influencing Postclassic centers like Cihuatán. Archaeological findings reveal the centrality of Nahua deities, including Tláloc, in their worldview. Atypical representations of Tláloc, lacking in-depth archaeological studies, have been reported in Cihuatán. Objective: To initiate the investigation and interpretive analysis of five iconographic pieces of Tláloc in Cihuatán, exploring similarities with the observation of the jaguar and puma, felines relevant to the Nahua-Pipil culture of the Postclassic period. Method: Iconographic analysis of five Tláloc pieces from Cihuatán, comparing their iconography with the Nahua tradition. Observation of the jaguar and puma's features, seeking visual and conceptual parallels that may have influenced the local representation of the deity in the Postclassic. Results: The initial analysis reveals variations in the traditional iconography of Tláloc in the Cihuatán pieces. Possible similarities are identified between certain features of these representations and characteristics of the jaguar and puma, animals significant to the Nahua-Pipil cosmovision. Conclusion: This initial approach suggests a potential influence of local fauna, the jaguar and puma, on the representation of Tláloc in Cihuatán during the Postclassic period. A new line of archaeological and interpretive research is opened to better understand the adaptation of Nahua deities in Central America and their connection to the natural environment.